MIGRATION, COLONIALISM, AND SOCIAL IDENTITY: Mandailing Ethnic Group in Indonesia and Malaysia Since the 19th Century - Irsyad, Muhammad Rifqi (Journal of Contemporary Islam and Muslim Societies, 2025)
In the mid-19th century, a significant number of Mandailing ethnic groups migrated to Malaysia. Therefore, this study aimed to investigate the factors of Mandailing migration to Malaysia and examine how the decision to migrate impacted social identity development. A comparison was also made with social identity of Mandailing ethnic group in Indonesia. This study was based entirely on secondary data from books and scientific articles. The results showed significant differences in the development of Mandailing ethnic social identity in Indonesia and Malaysia, particularly in relation to the definition of ethnicity and various cultural aspects. These differences became more pronounced with the strengthening of the Dutch and British colonial powers, with each adopting different policies toward the indigenous population. Regarding ethnicity, the policies continued largely unchanged after both countries gained independence. More recently, after the 1990s, there has been a significant strengthening of ethnic awareness and the consolidation of several aspects of Mandailing ethnic social identity on both sides of Malacca Strait.Keywords: Mandailing, ethnicity, social identity, Indonesia, Malaysia